Feasibility of Single Barrel Heave Compensator 5MT - Azarol Nazwi, Azril Aiman (IRC, 2021)
In nowadays advancing technology era especially in Oil and Gas industry, many equipment, systems, and tool have been upgraded to achieve full effectiveness and reliability towards the industry as it affected on how business operating.